Application of Theory in Studies of Healthcare Built Environment Research. (July 2020) - Shannon, Michelle M.; Nordin, S.; Bernhardt, J.; Elf, M.
We aimed to examine the nature and extent of theory application in studies of built environment attributes and impact on adults in healthcare facilities. Many varied theories are described when providing the rationale for research into built environments in healthcare. Uncertainty exists around the right theory to frame a research question, alignment with measurement tools, and whether healthcare setting makes a difference. This poses challenges to researchers seeking to build the evidence base for built environment design that benefits patients and staff. Our multidisciplinary review team scoped the literature to determine how theories are used to inform research investigating the impact of the built environment of healthcare on adults. When researchers recorded theory at development of the study question, in data collection, and in data analysis/interpretation, we called this explicitly theory-based application. Synthesis occurred using a narrative approach. Overall, we found 17 diverse theories named in studies. Explicitly theory-based use occurred with eight theories, comprising 47% of all theories used. Five theories were named more frequently in studies out of all theories identified. In 20% of studies, theory was not used explicitly during the research inquiry. We argue that researchers must continue to strive toward explicit use of theories, similar to development of other health interventions that employ multifactorial components.